The influence of organizational citizenship behavior (OCB) and work environment on employee performance through work stress in the Library and Archives Office Sungai Penuh City - Yannizar Yannizar; Despri Wandi; Riki Sastiawan Putra; Metri Deritalina; Shinta Mutiara Zalfitri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Having employees with good performance can make it easier for organizational leaders to direct them to achieve organizational goals. The problem that develops in the Sungai Penuh City Library and Archives Office is that the achievement of performance targets has not been optimal, this is caused by some employees who have not implemented OCB behavior, the work environment and some employees who experience work stress. The purpose of this study was to analyze the effect of OCB on work stress, work environment on work stress, OCB on performance, work environment on performance, work stress on performance, OCB on performance through work stress, and work environment on performance through work stress. The respondents of this study amounted to 48 (forty-eight) employees of the Sungai Penuh City Library and Archives Office. Data analysis using path analysis with SPSS data processor version 25. The results showed that OCB has no effect on work stress, work environment has no effect on work stress, OCB affects performance, work environment affects performance, work stress affects performance, OCB affects performance through work stress, and work environment does not affect performance through work stress.